Ecophysiology and global dispersal of the freshwater SAR11-IIIb genus Fontibacterium - Fernandes, Clafy; Haber, Markus; Layoun, Paul; Chiriac, Maria-Cecilia; Bulzu, Paul-Adrian; Ghai, Rohit; Kasalicky, Vojtech; Shabarova, Tanja; Grossart, Hans-Peter; Woodhouse, Jason; Piwosz, Kasia; Alonso, Cecilia; et al. (Nature microbiology, 2025)
The SAR11-IIIb genus Fontibacterium within the order 'Ca. Pelagibacterales' is recognized for its ubiquitous presence in freshwater environments. However, cultivation limitations have hampered deeper ecophysiological understanding of this genus, with most data limited to lakes in the Northern Hemisphere. Here we present seven isolates representing two previously undescribed species, along with 93 high-quality metagenome-assembled genomes (MAGs) derived from a global survey across five continents. Phylogenomic analysis revealed 16 species forming nine distinct biogeographic clusters, indicating speciation patterns linked to water temperature and latitude. We observed endemic species restricted to African lakes, and quasi-endemic species confined to the Northern or Southern Hemisphere, which co-exist alongside cosmopolitan species. Metabolic profiling and growth experiments uncovered species- and strain-specific adaptations for nutrient uptake, along with unique pathways for sulfur metabolism. These findings provide a global-scale genomic and ecological overview for this underexplored lineage of freshwater SAR11.
Keywords: fylogeografie; Phylogeny; RNA ribozomální 16S; Genome, Bacterial; genom bakteriální; Metagenome; metagenom; RNA, Ribosomal, 16S; sladká voda; Fresh Water; Phylogeography; fylogeneze; jezera; Lakes